Ermi Suryani - Ermi Suryani Harahap; Nur Hotia Harahap; Rully Trihantana (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
Management is formed by professional experts together with the Mosque Prosperity Council that already exists in each village. In distributing the collected funds, the zakat officer do it productive and consumptive. zakat recipient is only for the elderly poor or other who are unable to work. National standard management and governance so that productive distribution continues to produce independent zakat recipient and new entrepreneurs. This research method is qualitative descriptive with the primary data used being statements of Indonesian rural recipient zakat obtained through interviews and forms of zakat organizational management in Indonesian rural mosques. The secondary data used are books on zakat and journals. The results of this study are five things that must be done by organizations to realize the acceleration of zakat potential in Indonesia, including: first, zakat officer must be competent in managing zakat consumptive and productive. Second, zakat treasurers are competent in recording sharia finances, have the expertise to find zakat giver and productive. Third, the secretary is competent in management ZIS and general. Fourth, the zakat officer must be an expert in entrepreneurship and graduate with a background in Islamic business management. Fifth, the team work zakat officer in managing the zakat recepient business prioritizes young mosque teenagers.